Preparing for a Vendetta: Family Feuds in Medieval Tuscany - Szolnoki, Zoltán (Before the Battle, 2023)
According to contemporary chroniclers, street fights were daily events in medieval Tuscan cities. In an urban environment, mental and tactical preparedness was necessary, although it was also important to know the inner politics of the city. The background of these conflicts was primarily described by the great urban history writers such as Giovanni Villani and Dino Compagni, but there are also special type sources, the so-called ricordanze, that show different elements of this micro-warfare phenomenon. These sources, which can be defined as merchant diaries, had a more personal viewpoint than the great chronicles, and as for the studies on the roots of the conflicts, it was more practical. The Velluti-Mannelli vendetta which happened in 1295 – written down by Donato Velluti – tells us about conscious time and place planning. The attacks had to be prepared not just politically and tactically, but from the economical point of view, too – which also transpires from the chronicle of Luca di Firidolfi da Panzano, who wrote about the hunting for his father’s murderers. The avengers travelled hundreds of kilometres and used the tools of medieval scouting and spycraft. In this paper, I explain and examine the thoughts of the ricordanze authors and conclude my article with a discussion on conflict resolution strategies. Although for medieval writers the most important elements were the fights, based on the parts of the ricordanze that mention the background of the feuds and the logical structure of the narratives we can also examine the situations that led to the war. Thus, we can attempt to analyse the families’ strategies associated with the preparation for conflict and the orchestrating of the raids and combats.